Corporate finance theory and practice. - Vernimmen, Pierre; Quiry, Pascal; Le Fur, Yann (John Wiley & Sons, Inc., 2022)
Get a distinctly European take on corporate finance The newly revised Sixth Edition of Corporate Finance: Theory and Practice delivers a uniquely European perspective on the foundations and latest trends in corporate finance, including the marked shifts brought about by sustainability, environmental, and social concerns. Containing updated statistics and graphs, the book covers the latest innovations in financial practice, like the rise of private equity investment, the continuous decline in listed companies, and the dramatic surge of sustainability-linked financing products. Readers get access to an accompanying website that offers regularly updated statistics, graphs, and charts, direct email access to the authors, quizzes, case studies, articles, and more. The book also includes: A balanced blend of theory and practice from an author team with a presence in academia and business Access to The Vernimmen.com Newsletter, which provides monthly updates on corporate finance to over 60,000 subscribers Ideal for students studying corporate finance as part of an MBA or a master's level programme in Finance, Corporate Finance: Theory and Practice is also required reading for practicing professionals in the UK and continental Europe seeking a distinctly European treatment of a critically important subject.